2013
DOI: 10.1158/0008-5472.can-12-3831
|View full text |Cite
|
Sign up to set email alerts
|

The Endogenous Tryptophan Metabolite and NAD+ Precursor Quinolinic Acid Confers Resistance of Gliomas to Oxidative Stress

Abstract: Quinolinic acid is a product of tryptophan degradation and may serve as a precursor for NAD þ , an important enzymatic cofactor for enzymes such as the DNA repair protein PARP. Pathologic accumulation of quinolinic acid has been found in neurodegenerative disorders including Alzheimer and Huntington disease, where it is thought to be toxic for neurons by activating the N-methyl-D-aspartate (NMDA) receptor and inducing excitotoxicity. Although many tumors including gliomas constitutively catabolize tryptophan, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 58 publications
1
118
2
Order By: Relevance
“…Both deacetylation catalyzed by sirtuins and ADP-ribosylation are NAD+ consuming processes (19,20,21), making cells dependent on NAD+ synthesis through the salvage pathway and through the de novo pathway, in which QPRT plays a key role. In line with this, QPRT was reported to increase resistance of glioma brain cancer cells to radiation and oxidative stress, by activating an NAD+ salvage pathway (22).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Both deacetylation catalyzed by sirtuins and ADP-ribosylation are NAD+ consuming processes (19,20,21), making cells dependent on NAD+ synthesis through the salvage pathway and through the de novo pathway, in which QPRT plays a key role. In line with this, QPRT was reported to increase resistance of glioma brain cancer cells to radiation and oxidative stress, by activating an NAD+ salvage pathway (22).…”
Section: Introductionmentioning
confidence: 70%
“…In a study on QPRT in glioma brain cancer cells, QPRT was found to increase resistance to radiation and oxidative stress (22). QPRT expression increases with a higher degree of malignancy in glioblastoma and levels of QPRT correlated to an unfavorable prognosis (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the chromatin-modifying enzymes involved in DNA repair depend on metabolic intermediates as cofactors for their activity, thereby directly linking changes in cellular metabolism with DNA repair (30). Interestingly, high levels of NAD + (nicotinamide adenine dinucleotide) correlate with radioprotection of human glioma cells (31). Alterations in NAD + levels modulate DNA repair and NAD + is elevated under conditions of nutrient deprivation.…”
Section: Crypt Stem Cells Maintain Integrity Of the Si In Fasted Micementioning
confidence: 99%